Identification and analyzing of behaviourial factors affecting investors failure in Irans stock market - MohammadMahdi Bahrololoum; Elias Mobarhan; Soheil Fazeli (فصلنامه بورس اوراق بهادار, 2020)
In recent decades, identification and analyzing of behaviourial factors affecting investors failure is one of the most important subjects in investment markets. In this research, identification and analyzing the nature of behaviourial factors that cause investors failing at Iran’s stock market is studied. This researchs approach is qualitative and analytical methods is used for. This research from data collection aspect is survey using non-structured interviews and from conclusions usage view is applied. At the framework of this survey, cognitive mapping method is used to map 12 experts of Iran’s stocks market perceptions about the causes of investors failure. In analyzing this map, analyzing methods of cognitive maps is used. Finally conclusions showed that 27 factors affecting investors failure based on mostly 70 percent experts agreement. These 27 factors can be divided into two “Inefficient implementation of effective decision” and “Ineffective decision making" clusters. Also “Lack of adequate, effective and efficient knowledge”, “inefficient and inadequate experience”, and “inappropriate strategy layout” more than other factors affecting the investment failure agreed upon by the participants in the research.